Rabbits and the Specious Origins of Domestication. (March 2018) - Irving-Pease, Evan K.; Frantz, Laurent A.F.; Sykes, Naomi; Callou, Cécile; Larson, Greger
Abstract : Rabbits are commonly thought to have been domesticated in ∼AD600 by French monks. Using historical and archaeological records, and genetic methods, we demonstrate that this is a misconception and the general inability to date domestication stems from both methodological biases and the lack of appreciation of domestication as a continuum.